The double-edged sword of inflammation in inherited retinal degenerations: Clinical and preclinical evidence for mechanistically and prognostically impactful but treatable complications - Sarici, Kubra; Vyas, Aanal; Iannaccone, Alessandro (Frontiers in Cell and Developmental Biology, 2023)
We present retrospective data from our clinical research efforts of the past several years alongside a review of past and current clinical and preclinical data independently by several investigators supporting our clinical evidence for the importance of inflammation in inherited retinal degenerations (IRDs). We show how inflammation is a complicating factor in IRDs but, if recognized and managed, also a great opportunity to mitigate disease severity immediately, improve patient prognosis and quality of life, extend the treatment windows for gene-specific and agnostic therapeutic approaches, mitigate the impact of inflammatory complications on the accurate estimate of vision changes in IRD natural history studies, improve the chances of safer outcomes following cataract surgery, and potentially reduce the likelihood of inflammatory adverse events and augment the efficacy of viral vector-based treatment approaches to IRDs. Manuscript contribution to the field. Inflammation has been suspected to be at play in IRDs since the beginning of the 1900s and became a research focus through the early 1990s but was then largely abandoned in favor of genetic-focused research. Thanks to regained cognizance, better research tools, and a more holistic approach to IRDs, the recent reappraisal of the role of inflammation in IRDs has brought back to the surface its importance. A potential confounder in natural history studies and a limiting factor in clinical trials if not accounted for, inflammation can be managed and often offers an opportunity for immediately improved prognosis and outcomes for IRD patients. We present our retrospective clinical evidence for connections with a measurable secondary autoimmune component that can develop in IRDs and contribute to vision loss but is at least in part treatable. We also present ample lines of evidence from the literature corroborating our clinical observations at the preclinical level.